Health psychology in the age of social media: pointers for future research - Thomas Gültzow; Nida Gizem Yilmaz; Martina Benvenuti; Michèle D. Birtel; Špela Dolinšek; James Green; Nino Gugushvili; Jiajun Mo; Marie G. Oldeman; Kaiyang Qin; Keenan A. Ramsey; Christin Scholz; et al. (European Health Psychologist, 2026)
Social media has become ubiquitous in daily life, transforming how we interact, exchange information, and form relationships. This has spurred researchers, including in health psychology, to investigate a diverse range of topics. However, it has become clear that, given the complexity of studying social media effects and the diverse types of social media usage that can be investigated, multiple methods are needed for all relevant research questions. Therefore, the 2024 annual European Health Psychology Society (EHPS) Synergy Winter School focused on exploring and discussing a selected set of established and emerging research methods that can be used to study social media (effects) – such as neuroimaging, content analysis, and data donation – and the operationalization of social media usage as an important conceptual task. In this article we outline the methodological advantages and disadvantages and discuss themes that emerged from discussions with scholars in the field of social media research. In doing so, we aim to offer insights to guide future research related to measurement issues, interdisciplinary collaboration, diversity and representation, participant concerns, ethical considerations, and the topic of social media and mental health. Finally, we summarize key recommendations for conducting social media research, which may be applicable to health psychology and the social sciences more broadly.